Man vs Woman: Exploring Organizational Support, Job Satisfaction, and Trust in Travel Industry Employee Commitment - Renggi, Theresia Salsa Purnama; Yudhistira, Putu Gde Arie (Jurnal Aplikasi Manajemen, 2024)
Attention to employee welfare is a significant focus in human resource management. Companies that pay attention to employee welfare often see increased employee commitment. This study aims to analyze the direct and indirect effects of perceived organizational support on affective commitment in conventional travel agents in Bali, considering the mediating roles of job satisfaction and employee trust and the moderating role of gender. Data for this was collected through a questionnaire and a sample of 411 conventional travel agent employees in Bali. Sample selection was carried out using the purposive sampling method. The collected data will analyzed using SmartPLS 4. This study shows that perceived organizational support positively affects employees’ affective commitment at conventional travel agents in Bali. In addition, job satisfaction positively influenced employees’ affective commitment, but employee trust did not affect affective commitment. This finding also identified that job satisfaction partially mediates the relationship between perceived organizational support and affective commitment, while employee trust does not mediate the relationship. An interesting difference was seen between male and female employees. Perceived organizational support had a significant impact on female employees’ trust. This research implies that companies and management of conventional travel agencies should improve employee support, satisfaction, and well-being of male and female employees without discrimination.